Investing Decisions and Financial Performance of a Commercial Government Agency of South Africa - Sizwe Perfect Ayanda NTULI; Zwelihle Wiseman NZUZA (International Journal of Environmental, Sustainability, and Social Science, 2024)
The financial management of commercial government agencies in South Africa has been beset by challenges in achieving financial performance despite efforts to conserve financial position. Investment decisions present a potential strategy for improving financial performance. Guided by contingency theory, this study seeks to explore the perceptions of finance staff regarding the impact of investment decisions on the financial performance of a selected commercial government agency in South Africa. The study employs a cross-sectional, quantitative research design, utilizing a questionnaire to gather data from 51 respondents. Based on regression coefficients, the analysis reveals a strong positive causal relationship between investment decisions and financial performance. In particular, the beta coefficient indicates that investment decisions significantly predict financial performance (? = 0.827, p < .001). These findings suggest that firms should prioritize investment decisions to improve financial performance and promote growth. Accordingly, we recommend that commercial government agencies prioritize investment decisions to improve financial performance and achieve organizational goals.